Comparision Of Computing Tools For Control Of Future Illumination In Smart Grids - Taşkın, Sezai; Tansel, İbrahim N.; Gümüş, Metin; Uragun, Balemir (T.C. Bilim, Sanayi ve Teknoloji Bakanlığı, 2014)
Gün geçtikçe artan çevresel duyarlık ile beraber elektronik ekipman fiyatlarındaki azalma, yakın gelecekte aydınlatma sistemleri işletiminin ve tasarımının da değişeceği beklentisini oluşturmuştur. Bu çalışmada, akıllı cadde aydınlatması kavramı üzerinde durulmuştur. Çevrim tablosuna göre girdileri ve çıktıları belirlenen Yapay Sinir Ağları ve Bulanık Mantık algoritmaları bir cadde aydınlatma kontrolörünün davranışı simüle edilerek karşılaştırılmıştır. The design and operation of the street lights are expected to change in near future with the influence of reducing electronic component prices and increasing environmental consciousness. In this paper, networking intelligent street light (ISL) concept is discussed. The capabilities of look up table, neural networks and fuzzy logic are compared when they are used for a simulated street light controller. The look up table was the easiest to develop. The neural network smoothed the response curves and provided continuous transitions between the modes. The fuzzy logic allowed integration of many sensors more easily. However, evaluation and perfection of the responses when all the possible inputs were concerned were difficult.
Akıllı Şebelerde Geleceğin Aydınlatma Kontrolü İçin Hesaplama Araçlarının Karşılaştırılması
Keywords: Street Light; Neural Network; Fuzzy Logic; Solar Cell; LED Lights